The inhibitory effect of octreotide on experimental colorectal carcinogenesis - (:unkn) unknown (SPRINGER-VERLAG, 2002)
Purpose. This study was conducted to investigate the effect of octreotide on colorectal carcinogenesis by administering octreotide either alone or combined with polyglactin, which is a well-known suture material, on chemically induced colorectal cancer development in rats. Methods. A total of 72 rats were divided into six groups. Two groups were subjected to a colotomy and repair using polyglactin. Another two groups underwent a sham procedure. The fifth group received octreotide alone and the sixth group served as a control. Both groups of rats in the polyglactin and sham groups received octreotide additionally. Methylnitrosourea was administered rectally to all the animals at a dose of 4 mg/kg per week for 20 weeks to induce carcinogenesis. Octreotide was injected twice a day at a total daily dose of 100 mug/ka. The thymidine labeling index was used to assess the synthesis phase fraction in order to measure the cell proliferation rate. Results. The mean number of tumors per rat was significantly higher in the polyglactin group than in both the sham and control groups. It was significantly lower in the octreotide and polyglactin + octreotide groups than in the control and polyglactin groups, respectively. All the animals in the octreotide group had one tumor, while 66.6% of the control group had multiple tumors. The number of multiple tumors was significantly lower in the polyglactin + octreotide and sham + octreotide groups than in the polyglactin and sham groups, respectively. The mean tumor size in the octreotide group was significantly smaller than in the control group, whereas it was larger in the polyglactin group in comparison with the sham and control groups. It was also reduced in the polyglactin + octreotide group in comparison with the polyglactin group. The thymidine labeling index was significantly higher in the polyglactin group compared with both the sham and control groups, whereas it was lower in the octreotide group in comparison with the control group. The addition of octreotide administration to the polyglactin usage and the sham procedure significantly decreased the thymidine labeling indexes. Conclusion. These results indicate that octreotide reduces the frequency of tumor occurrence and has an inhibitory effect on its development in chemically induced experimental colorectal cancer. Octreotide can also reduce the enhancing effect of polyglactin on colorectal carcinogenesis when it is combined with polyglactin.
Keywords: octreotide; colorectal cancer; thymidine labeling index; polyglactin; THYMIDINE LABELING INDEX; HUMAN-COLON CANCER; GROWTH-FACTOR-I; SOMATOSTATIN ANALOGS; ANASTOMOTIC RECURRENCE; PANCREATIC-CANCER; SUTURE MATERIALS; BREAST-CANCER; RECEPTORS; CARCINOMA